PENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL JIGSAW DENGAN PERMAINAN PUZZLE DALAM PEMBELAJARAN IPS KELAS IV SDN KABUPATEN AGAM - Febrina, Trisma Lidia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research aim was to describe for improve students’ learning achievement with Jigsaw approach with puzzle game at primary school in Cingkariang Banuhampu. This study was a classroom action research consisting of two cycles. Each cycles consisted of planning action, observation, and reflecting. This data analyzed by using qualitative and quantitative approch. The subject at class student of IV SDN 13 Cingkariang with 24 student. The result of the research showed improve learning achievement with Jigsaw approach with puzzle game. Kata kunci : hasil belajar siswa; model jigsaw ; permainan puzzle